Pengaruh Subtitusi Tepung Terigu dengan Tepung Bayam Merah (Amaranthus Tricolor L.) pada Pembuatan Mie Basah terhadap Daya Terima dan Nilai Gizi - Amimi, Aina; Anwar, Asrul; Azwar, Azwar (3031-8572, 2024)
Noodles, one of the food products with wheat flour raw materials, is very popular among the people of Indonesia. Noodle products are generally used as an energy source because they have quite high carbohydrates. Noodles are also one of the types of alternative foods after rice whose development is very fast. Noodles develop over time in terms of number and variety (Tiffani et al. 2018). The purpose of this study is the discovery of the addition of red spinach flour (Amaranthus tricolor L. ) to the acceptability and nutritional value of wet noodles. This study aims to examine the differences in wet noodles substitution of red spinach flour on acceptability and nutritional value (moisture content, fiber content, protein, carbohydrates, ash content, fat). This study is an experimental study with four treatments of plain bread substitution of red spinach leaf flour A1 (100% wheat flour: 0% red spinach flour), A2 (95% wheat flour: 5% red spinach flour), A3 (90% wheat flour: 10% red spinach flour), A4 (85% wheat flour: 15% red spinach flour). Organoleptic test data were analyzed with a Complete Randomized Design (RAL) and nutritional value tests with descriptive tests. Conducted at the Food and Nutrition Laboratory of the Baiturrahim Jambi College of Health Sciences in July and the Nutritional Value Test at the Laboratory of the Faculty of Animal Husbandry Unja in August. The results showed that the selected red spinach flour substitution wet noodles (90% wheat flour: 10% red spinach flour) had a preferred color, aroma, texture and taste. In this study, it can be concluded that there is a significant difference in the substitution of red spinach flour wet noodles to the acceptability and nutritional value of the wet noodles.